Ultrasensitive quantitation of Paraquat based on a small molecule-induced dual-cycle amplification strategy - Chen, Hao-Ran; Zhang, Shun; Chen, Tao; Yang, Wei-Guo; Su, Ming-Li; Fu, Guan-Yan; Yi, Wei-Jing; Yuan, Ruo; Xu, Shang-Cheng; Liang, Wen-Bin (Biosensors & bioelectronics, 2023)
Paraquat (PQ) is a typical biotoxic small molecule. Knowledge of how to directly introduce it into cyclic amplification rather than transform it into a secondary target is lacking in current analytical methods. Considering the urgent need for trace pesticide residue detection and the inherent defects of small molecule analysis, a CRISPR/Cas12a-driven small molecule-induced dual-cycle strategy was developed based on the immune competition method. The key to signal amplification is the mutual activation and acceleration between Cycle 1 triggered by the small molecule and Cycle 2 driven by CRISPR/Cas12a. Impressively, small molecules have been successfully incorporated into the dual-cycle strategy, which achieves a low detection limit (3.1 pg/mL) and a wide linear range (from 10 pg/mL to 50 μg/mL). Moreover, the designed biosensor was successfully employed to evaluate the PQ residual level in real samples and showed effective implementation for the bioanalysis of small molecule targets and pesticide residue-related food safety.